2020
DOI: 10.2147/ijn.s213079
|View full text |Cite
|
Sign up to set email alerts
|

<p>Glucose-coated Berberine Nanodrug for Glioma Therapy through Mitochondrial Pathway</p>

Abstract: Introduction: Glioma is the primary malignant brain tumor with poor prognosis. Berberine (BBR) was the potential drug for anti-tumor in glioma cells. Based on its limitation of poor aqueous solubility and instability, little information of BBR nanoparticles is reported in glioma. Methods: Different solutions including 5% glucose, 1*PBS, ddH 2 O, 0.9% NaCl, cell culture medium were selected, and only 5% glucose and ddH 2 O exhibited BBR-related nanoparticles. After heating for a longer time or adding a higher c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…BBR emits a yellowish fluorescence (excitation: 488nm, emission: 564nm) ( 46 , 47 ), and its uptake was examined using the Infinite M1000 microplate reader (Tecan Trading AG, Männedorf, Switzerland) and confocal microscopy. The cells were treated with BBR, OPCs, or their combination for 24 hours, and washed two times with cold phosphate buffered solution (PBS) before measurement.…”
Section: Methodsmentioning
confidence: 99%
“…BBR emits a yellowish fluorescence (excitation: 488nm, emission: 564nm) ( 46 , 47 ), and its uptake was examined using the Infinite M1000 microplate reader (Tecan Trading AG, Männedorf, Switzerland) and confocal microscopy. The cells were treated with BBR, OPCs, or their combination for 24 hours, and washed two times with cold phosphate buffered solution (PBS) before measurement.…”
Section: Methodsmentioning
confidence: 99%
“…It also was low cost, and had a long history of safe clinical application (Sandeep and Nandini, 2017 ; Ju et al, 2018 ; Imenshahidi and Hosseinzadeh, 2019 ; Suadoni and Atherton, 2021 ). In addition, BBR can penetrate the BBB successfully (Wang et al, 2005 , 2020 ; Simoes Pires et al, 2014 ; Abdel Moneim, 2015 ; Zhou et al, 2016 ) and may pass through the blood–retinal barrier which has similar structures.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that silibinin has extremely high antioxidant and anti-tumor properties, it has drawn our attention to its potential use in the treatment of GBM.BNIP3, a member of the Bcl-2 family of pro-apoptotic proteins and a receptor for mitophagy, exhibits context-dependent roles in cancer (Gorbunova et al, 2020;Gorbunova et al, 2020;Vara-Perez et al, 2021).It targets mitochondria and could induce mitochondrial damage and nuclear translocation of AIF6 (Su et al, 2016). A study using GBM cell lines and nude mice with xenografted GBM has confirmed that silibinin could induce mitophagy in GBM, and that autophagy can promote silibinin-induced BNIP3 overexpression and its accumulation in the mitochondria, thereby triggering AIF-dependent death in GBM cells (Wang et al, 2020b). Moreover, silibinin has also been shown to inhibit GBM cell migration by inhibiting MMP-2 and -9 and improving TMZresistance in GBM cells (Zhai et al, 2021;Wong et al, 2023).…”
Section: Silibininmentioning
confidence: 90%